Effect of temperature on Sclerotinia sclerotiorum (Lib.) de bary growth in vitro - Shevchuk, O.; Afanasieva, O.; Kryvosheiev, S.; Zlenko, D.; Hryhorenko, I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal of this study was to determine the optimal temperature for mycelial growth and sclerotia formation of Sclerotinia sclerotiorum, the causal agent of white mold, under laboratory conditions when cultivated on potato dextrose agar (PDA).Methods. The research was conducted using laboratory, analytical, and statistical methods. The isolate used in the study was obtained from a sunflower head affected by white mold. Mycelial growth and sclerotia formation were studied across a temperature range of 5 to 30°C.Results. It was established that the pathogen develops within the temperature range of 5—25°C, at 30°C no mycelial growth was observed. The most intensive colony growth occurred at 25°C, whereas the highest number of sclerotia formed at 20°C. The greatest sclerotial mass was recorded at 15°C. Significant differences in colony growth rate and sclerotia formation were found depending on the incubation temperature. The highest radial growth rate was observed at 20—25°C, while the lowest was at 5°C. A clear inverse relationship between temperature and sclerotia development time was observed: as the temperature decreased, growth rate slowed and sclerotia formation was delayed. Cultivation at 20°C resulted in the highest number of sclerotia, while both higher and lower temperatures reduced their quantity. In contrast, sclerotial mass was highest at 15°C, with both increased and decreased temperatures resulting in smaller sclerotia. The effect of prior low-temperature cultivation (at 5°C) on subsequent growth was also studied. The results showed that brief exposure to low temperatures did not lead to significant changes in colony growth or sclerotia formation.Conclusion. Sclerotinia sclerotiorum is capable of developing within a temperature range of 5—25°C. The optimal temperature for cultivation on potato dextrose agar in vitro is 20°C, which ensures both intensive mycelial growth and the highest number of sclerotia. These findings can be used to improve protocols for producing infection material for artificial inoculation in phytopathological studies and for studying the pathogen’s biology in the context of climate change.